The bacterial flora of abscesses in domestic animals in Selangor - Bahaman, Abdul Rani; Basri, K.; Majid , M. Shah; Sheikh Omar, Abdul Rahman (Persatuan Doktor Veterinar Malaysia, 1985)
Two hundred and thirty five cases o[ abscesses [rom domestic animals were seen at the Veterinary School, Universiti Pertanian Malaysia during the period [rom 1976 to 1983. Three hundred and seven aerobic bacteria were isolated, 133 of which were in pure cultures. Corynebacterium pyogenes was the most common species (38.1%) isolated, [allowed by Staphylococcus pyogenes (27.4%), streptococci (10.4%), Escherichia coli (6.8%) and Proteus spp. (4.6%). In small animals, Staphylococcus pyogenes was the commonest species. A high prevalence of caseous lymphadenitis caused by Corynebacterium ovis was seen in the small ruminants whilst melioidosis caused by Pseudomonas pseudo mallei was seen in swine. Since Gram positive bacteria (79.5%) were mainly responsible [or abscesses studied, it is suggested that chemotherapy is directed against this group of bacteria when facilities [or bacterial isolation and identification are not available.